Retired French Military Orthopedic Surgeons' Opinions on Their Careers - de l'Escalopier, Nicolas; Barbier, Olivier; Mathieu, Laurent; Rongieras, Frédéric; Choufani, Camille (Military medicine, 2022)
Owing to their professional and personal experiences, retired military orthopedic surgeons' views of their careers are a unique source of inspiration. Reflecting on their experiences allows them to grasp the positive points and those that need to be improved for future generations. The purpose of this study is to gather the opinions of retired surgeons on the career of military orthopedic surgeons. We addressed a questionnaire to all retired French military orthopedic surgeons in the database of the Chair of Applied Surgery for the Armed Forces as of December 2020, retrained in the civilian sector. A questionnaire sent by email made it possible to collect demographic, professional, and personal data about their careers. Subjective data were evaluated using a visual analog scale from 0 to 10 or a subjective qualification scale. The main assessment criterion was the average score (out of 10) of the retired surgeons' opinions on their careers. Fifty-two percent of retired surgeons replied (32 out of 61), with the respondents having an average age of 63 years. They had been in military retirement for an average of 14 years and had practiced for approximately 13.5 years. The majority (28 out of 32) had had a civilian activity after leaving the army. The three main reasons for leaving were the unsatisfactory working environment, the high number of deployments, and insufficient pay. Nevertheless, the respondents were satisfied with their activity, their job, and their training. The average score given for the overall opinion on their careers was 8.14/10. The three main disadvantages of the career that were noted were the quality of family life, the conditions of employment, and the financial aspects. The majority were very satisfied with the second half of their civil career. Overall, the opinion of retired French military orthopedic surgeons on their careers is very good. Their point of view provides interesting elements for reflection from both a professional point of view and a personal point of view. They were very satisfied with the quality of their training, their job, and their activity. However, the quality of their personal/family life, working conditions, and the financial aspects of the career reduced this satisfaction. The results also have potential application in improving the preparation of young military orthopedic surgeons.